Kesalahan Sintaksis pada Teks Tanggapan Kelas IX B SMPN 12 Malang - Ersita Noor Mahliga; Sumadi; Novi Eka Susilowati (JoLLA: Journal of Language, Literature, and Arts, 2021)
Abstract: This research aims to describe the syntactic errors in the response text of class IX B SMPN 12 Malang. This research uses a descriptive qualitative approach. The data were analyzed using the Miles and Huberman model with three sub activities, namely (1) data reduction, (2) data presentation, and (3) conclusion drawing. The results of the data analysis on the syntactic errors found in the response text of class IX B SMPN 12 Malang took the form of (1) errors at the phrasal level and (2) sentences. Errors at the phrasal level include (1) incorrect use of prepositions, (2) excessive use of elements, (3) inappropriate use of elements, (4) improper wording, and (5) double pluralization. Syntactic errors at the sentence level include (1) ambiguous sentences, (2) illogical sentences, (3) inappropriate use of conjunctions, (4) excessive use of conjunctions, (5) omission of conjunctions, (6) zero-subject sentences, (7) unpredicated sentences, (8) use of prepositions in transitive verbs, (9) use of unnecessary interrogative words, and (10) incomplete sentences. Keywords: language errors, syntax errors, response text Abstrak: Penelitian ini bertujuan mendeskripsikan kesalahan sintaksis dalam teks tanggapan kelas IX B SMPN 12 Malang. Penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif. Analisis data menggunakan model Miles dan Huberman dengan tiga alur kegiatan, yaitu (1) reduksi data, (2) penyajian data, dan (3) penarikan kesimpulan. Hasil penelitian kesalahan sintaksis pada teks tanggapan kelas IX B SMPN 12 Malang meliputi (1) kesalahan pada tataran frasa, dan (2) kalimat. Kesalahan pada tataran frasa meliputi (1) kesalahan penggunaan preposisi, (2) penggunaan unsur yang berlebihan, (3) penggunaan unsur yang tidak tepat, (4) susunan kata yang tidak tepat, dan (5) penjamakan ganda. Kesalahan sintaksis pada tataran kalimat meliputi (1) kalimat rancu, (2) kalimat tidak logis, (3) penggunaan konjungsi yang tidak tepat, (4) penggunaan konjungsi yang berlebihan, (5) penghilangan konjungsi, (6) kalimat tidak bersubjek, (7) kalimat tidak berpredikat, (8) penggunaan preposisi pada verba transitif, (9) penggunaan kata tanya tidak perlu, dan (10) kalimat tidak lengkap. Kata kunci: kesalahan berbahasa, kesalahan sintaksis, teks tangga